1995
DOI: 10.2135/cropsci1995.0011183x003500050020x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Defeciency in Maize: I. Effects on Crop Growth, Development, Dry Matter Partitioning, and Kernel Set

Abstract: Variations in N availability affect growth and development of maize (Zea mays L.) and may lead to changes in crop physiological conditions at flowering and in kernel set. The objectives of this study were (i) to establish the effect of N availability on crop development, crop radiation interception, radiation use efficiency, and dry matter partitioning; and (ii) to study the relationship between kernel number and crop growth at flowering and between kernel number and crop N accumulation at flowering. Three exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
172
3
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(205 citation statements)
references
References 0 publications
23
172
3
7
Order By: Relevance
“…Decreased TDM production due to N shortage in the maize plants was found to be associated with reductions in leaf photosynthetic capacity as earlier observed by Uhart and Andrade (1995) and it was mainly ascribed to a smaller total N content and GB content in the plants (Figures 1 and 2). The ameliorative effects of GB and HA on most plants exposed to various stresses have been widely reported in the literature (Chen & Aviad 1990;Demiral & Turkan 2004;Ashraf & Foolad 2007;Cimrin et al 2010).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Decreased TDM production due to N shortage in the maize plants was found to be associated with reductions in leaf photosynthetic capacity as earlier observed by Uhart and Andrade (1995) and it was mainly ascribed to a smaller total N content and GB content in the plants (Figures 1 and 2). The ameliorative effects of GB and HA on most plants exposed to various stresses have been widely reported in the literature (Chen & Aviad 1990;Demiral & Turkan 2004;Ashraf & Foolad 2007;Cimrin et al 2010).…”
Section: Discussionsupporting
confidence: 75%
“…The mesophyllic activity is another cause of limiting maize leaf P n under NS (Cruz et al 2003). Decrease in P n due to N deficiency has been reported to be one of the major causes that limit plant growth and productivity (Uhart & Andrade 1995;Zhao et al 2003Zhao et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas situações em que a capacidade dos grãos em alocar fotoassimilados é o fator limitante, como em plantios mais precoces na Região Sul do Brasil, pode-se aumentar a densidade de plantas, para que haja um aumento na interceptação e conversão da radiação, de modo a promover um equilíbrio na relação fonte/dreno, sem que a taxa e a duração do período de enchimento de grãos sejam substancialmente alteradas (Daynard et al, 1971;Schoper et al, 1982;Magalhães & Jones, 1990a;Stewart et al, 1997). O aumento da densidade de plantas, nesse caso, seria acompanhado por um aumento do número de grãos por unidade de área, e não pelo aumento no número de grãos por planta, que parece ser predeterminado, refletindo o potencial genético da planta (Magalhães & Jones, 1990b;Uhart & Andrade, 1995). Apesar de tolerar altas densidades de plantas, os híbridos modernos são mais sensíveis a condições de estresse em anos com baixa precipitação pluvial, provocando diminuição na capacidade dos drenos em acumular os fotoassimilados disponíveis (Ouattar et al, 1987;Cox, 1996).…”
Section: Resultsunclassified
“…Uhart and Andrade (1995) indicated that the grain yield of maize was reduced by reduced application of nitrogen. It is important to use an optimum amount of water and nitrogen for best management of crop production in arid and semi-arid regions, because the application of an excess amount of water causes nitrogen leaching (Artiola, 1991).…”
mentioning
confidence: 99%